Differential diagnosis between chronic versus aggressive periodontitis and staging of aggressive periodontitis: A cross-sectional study - Srinivas Sulugodu Ramachandra; Vivek Vijay Gupta; Dhoom Singh Mehta; Kalyan C Gundavarapu; Nibali Luigi (Wolters Kluwer Medknow Publications, 2017)
Background: Differentiating between chronic periodontitis (CP) and aggressive periodontitis (AgP) is challenging. The aim of this study was to assess the variations in diagnosis between CP versus AgP and the staging of AgP based on the disease-staging index for AgP among periodontists, specialists in oral medicine, and general dental practitioners (GDPs). Materials and Methods: Fifteen cases diagnosed as either CP or AgP were included in a "case document" and sent electronically to 75 respondents. Case document included a detailed history with periodontal charting, clinical features, images, and radiographs for all the cases. Diagnosis and staging for the case (if diagnosed as AgP) were requested. A reordered case document (cases in a different sequence) was again sent to respondents after a gap of 1 month. Statistical analysis: Descriptive statistics including frequency and percentage were calculated. Pearson's Chi-square test was used to analyze the data collected. Results: For the "case document," 10.17% of the responses were different from those of the authors for diagnosis, whereas 4.48% of the responses were different from those of the authors for the staging of AgP. The agreement in the overall responses was in the range of 0.69-0.84, which was considered good. Comparison of the responses for diagnosis showed statistically significant (P = 0.009) difference between specialists in oral medicine and GDPs. Conclusions: Variations exist among respondents regarding the diagnosis of CP versus AgP. Staging of AgP based on the listed criteria showed low variations.